Simple Synthesis of New Bioactive Nitrogenous Compounds by In Silico Study - Amira Ait Belkacem (Chemistry Proceedings, 2024)
A new derivative of nitrogenous compounds was successfully synthesized through a simple reaction, resulting in an excellent yield. These molecules underwent theoretical simulation studies to verify their anti-Alzheimer and anti-cancer effects, such as acetylcholinesterase, and tubulin.